Synthesis of Oleic Acid Derivatives as Pour Point Depressant (PPD) - Nila Tanyela Berghuis; Zayed Abdulmalik Marwan; Agus Astra Pramana; Jati Arie Wibowo (Jurnal Kimia Sains dan Aplikasi, 2025)
Crude oil is widely used worldwide as an energy source in various fields. Over the years, crude oil production has decreased due to one major problem that continues to occur, namely wax deposition. Wax deposits tend to occur due to the composition of the crude oil itself. Crude oil mostly consists of large amounts of hydrocarbon compounds, such as paraffins. Therefore, an additive, such as a pour point depressant (PPD), is needed to inhibit or prevent wax formation. This study compares the performance of various PPDs synthesized using oleic acid as a base material. The esterification of oleic acid with alcohols yielded PPD-Ester Butanol (96.72%) and PPD-Ester Decanol (72.21%). Further esterification with oleic acid resulted in PPD-Ester Butanol + Oleic Acid (47.30%) and PPD-Ester Decanol + Oleic Acid (22.56%). These derivatives can undergo additional reactions, such as epoxidation, diol formation, and esterification, to produce a PPD. Pour point measurements on crude oil samples were conducted following ASTM D-5853. The blank sample had a pour point of 39°C. PPD-Ester Decanol reduced the pour point by 3°C, while all PPD-Esters further esterified with oleic acid lowered it by 9°C. Chemical characterization via FTIR analysis confirmed the presence of C=C, C=O, and aliphatic C-H functional groups. GC-MS analysis of PPD-Ester Decanol + Oleic Acid (decyl 9-monooleate, 10-hydroxy oleate) identified three major compounds: 1-decanol, oleic acid, and decyl oleate. Physical characterization revealed that the synthesized PPDs had densities ranging from 850 to 1,066 kg/m3.